The Expansion of Wasiat Wajibah: Protecting Legal Certainty and Fairness in Indonesian Inheritance Law - Mohamad Yamin; Fauzan Ali Rasyid; Ending Solehudin; Ahmad Zaini (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
Article 209 of the Compilation of Islamic Law normatively limits the recipients of wasiat wajibah ‘mandatory bequests’ only to adopted children and adoptive parents with a maximum limit of one-third of the testator's property. However, the development of the Supreme Court's jurisprudence shows that there is an expansion of the recipients of compulsory probate to other parties such as stepchildren, children from unregistered marriages, and non-Muslim heirs, which creates a gap between written norms and judicial practice. This study aims to analyze the legal considerations of the Supreme Court in expanding the subject of compulsory probate recipients and its contribution to the renewal of probate law in the development of national law. The research uses an empirical juridical approach with data collection techniques through documentation studies of Supreme Court decisions, laws and regulations, and legal literature, which are analyzed descriptively- analytically using maqāṣid al-sharī'ah theory, legal reform theory, and legal discovery theory; validation is done through triangulation of primary and secondary legal sources. The results show that the Supreme Court's consideration in expanding the mandatory bequests is based on the recipient's real contribution to the testator, social proximity, and protection of vulnerable parties for the sake of substantive justice. Theoretically, this research contributes to the development of the concept of maqāṣid al-sharī'ah-based mandatory bequests and strengthens the legitimacy of jurisprudence as an instrument of Islamic law reform in Indonesia's national legal system, especially in bridging the tension between normative norms and social reality.